A Comparative Study of KUHAP and the Draft KUHAP on the Protection of Human Rights in Criminal Justice Processes - Winoto, Taufik Pandan (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze and compare the Indonesian Criminal Procedure Code (KUHAP) and the Draft Criminal Procedure Code (RKUHAP) in the context of human rights protection within criminal justice processes in Indonesia. The research employs a qualitative approach using library research methods, focusing on statutory analysis, legal documents, and relevant academic literature. The findings reveal that KUHAP still shows significant limitations in ensuring comprehensive human rights protection, particularly regarding the right to legal counsel from the early stage of investigation, prohibition of torture, and protection of crime victims. In contrast, RKUHAP introduces substantial normative reforms by reinforcing the principles of due process of law and fair trial, aligning with international human rights instruments such as the International Covenant on Civil and Political Rights (ICCPR). The study concludes that RKUHAP represents a crucial step toward a more just, humane, and human rights–oriented criminal justice system. However, its practical effectiveness largely depends on the readiness of law enforcement institutions and the broader legal culture within Indonesian society.